2021
DOI: 10.20944/preprints202111.0485.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis on Spatio-temporal Characteristics and Influencing Factors of Industrial Green Innovation Efficiency——From the Perspective of Innovation Value Chain

Abstract: Green innovation has become an important combination of high-quality economic growth and sustainable development of ecological environment. In this paper, the super-efficiency network SBM model is used to measure the two-stage green innovation efficiency of industrial science and technology R&D and achievement transformation in 30 provinces and cities from 2009 to 2019, and exploratory Data Analysis (ESDA) and spatial econometric model are used to investigate the spatial-temporal evolution characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Based on the SBM (Slack-Based Model) model, Tone further proposed the super-efficient SBM model (Super-SBM), which solves the problem of difficult sorting and comparison when multiple decision units being evaluated reach the effective value of 1 [16] . As the research progressed, it was found that the SBM model and other DEA models usually treat the production behavior of enterprises as a "black box" for single-stage efficiency measurement, and the measurement results and analysis lack realistic guidance [17] . In response to this problem, Tone constructed the network SBM model, a non-radial, non-angle efficiency measurement model based on slack variables, which can measure not only the overall efficiency value of the decision unit, but also the stage efficiency value, which is conducive to researchers to comprehensively analyze the technological innovation efficiency of the research object and make objective accurate judgment [18] .…”
Section: Two-stage Super-nsbm Modelmentioning
confidence: 99%
“…Based on the SBM (Slack-Based Model) model, Tone further proposed the super-efficient SBM model (Super-SBM), which solves the problem of difficult sorting and comparison when multiple decision units being evaluated reach the effective value of 1 [16] . As the research progressed, it was found that the SBM model and other DEA models usually treat the production behavior of enterprises as a "black box" for single-stage efficiency measurement, and the measurement results and analysis lack realistic guidance [17] . In response to this problem, Tone constructed the network SBM model, a non-radial, non-angle efficiency measurement model based on slack variables, which can measure not only the overall efficiency value of the decision unit, but also the stage efficiency value, which is conducive to researchers to comprehensively analyze the technological innovation efficiency of the research object and make objective accurate judgment [18] .…”
Section: Two-stage Super-nsbm Modelmentioning
confidence: 99%
“…In addition, the coal-dominated energy consumption structure of enterprises can only achieve substantial transformation through technological innovation. In turn, the transformation of energy consumption supply and demand structure further stimulates the sustainable development of green technology innovation [30]. Therefore, the author proposes the following hypothesis:…”
Section: Assumptions About the Impact Of Green Technology Innovation ...mentioning
confidence: 99%